Clinical analysis of contributors to the delayed gallbladder opacification following the use of water-soluble contrast medium - Ku MC; Kok VC; Lee MY; Hsu SM; Lee PY; Chang CW; Tyan YS; Juan CW (Dove Medical Press, 2016)
Ming-Chang Ku,1,2 Victor C Kok,3,4 Ming-Yung Lee,5 Soa-Min Hsu,1 Pei-Yu Lee,1 Che-Wei Chang,1 Yeu-Sheng Tyan,6 Chi-Wen Juan7,8 1Department of Radiology, Kuang Tien General Hospital, Taichung, 2Department of Nursing, Jen-Teh Junior College of Medicine, Nursing and Management, Miaoli, 3Department of Internal Medicine, Division of Medical Oncology, Kuang Tien General Hospital, 4Department of Bioinformatics and Medical Engineering, Asia University, 5Department of Statistics and Informatics Science, Providence University, 6Department of Medical Imaging, Chung Shan Medical University Hospital, 7Department of Emergency Medicine, Kuang Tien General Hospital, 8Department of Nursing, HungKuang University, Taichung, Taiwan Objectives: Gallbladder opacification (GBO) on computed tomography (CT) imaging may obscure certain pathological or emergent conditions in the gallbladder, such as neoplasms, stones, and hemorrhagic cholecystitis. This study aimed to investigate the clinical contributing factors that could predict the presence of delayed GBO determined by CT.Methods: This study retrospectively evaluated 243 consecutive patients who received enhanced CT or intravenous pyelography imaging and then underwent abdominal CT imaging within 5 days. According to the interval between imaging, the patients were divided into group A (1 day), group B (2 or 3 days), and group C (4 or 5 days). Three radiologists evaluated CT images to determine GBO. Fisher’s exact test and multivariate backward stepwise elimination logistic regression were performed.Results: Positive GBO was significantly associated with the interval between imaging studies, contrast type, contrast volume, renal function, and hypertransaminasemia (P<0.05). Multivariate backward stepwise elimination logistic regression analysis of the three groups identified contrast type and hypertransaminasemia as independent predictors of GBO in group B patients (odds ratio [OR], 13.52, 95% confidence interval [CI], 1.72–106.38 and OR, 3.43, 95% CI, 1.31–8.98, respectively; P<0.05). Hypertransaminasemia was the only independent predictor of GBO in group C patients with an OR of 7.2 (95% CI, 1.62–31.73). Hypertransaminasemia was noted in three patients (100%) who initially underwent imaging 5 days prior to GBO.Conclusion: Delayed GBO on CT imaging may be associated with laboratory hypertransaminasemia, particularly in patients receiving contrast medium over a period of ≥4 days. A detailed clinical history, physical examination, and further workup are of paramount importance for investigating the underlying cause behind the hypertransaminasemia. Keywords: logistic regression, hemorrhagic cholecystitis, vicarious contrast medium excretion, computed tomography, hypertransaminasemia